2007
DOI: 10.1007/s10067-007-0738-3
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept in the treatment of rheumatoid arthritis: clinical follow-up over one year by ultrasonography

Abstract: We evaluated clinically and sonographically the effects of etanercept therapy in patients with rheumatoid arthritis (RA) over 12 months of treatment. Eighteen patients affected by RAwho were non-responders or partial responders to disease modifying therapy were commenced on Etanercept treatment. Before starting therapy (T0) and at 12 months (T1), the following parameters were evaluated: erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), visual analogue scale (VAS) for pain, number of painful and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 41 publications
3
30
0
3
Order By: Relevance
“…Our results were in accordance with those of previous longitudinal studies that have shown changes in CDUS or PDUS findings associated with clinical and laboratory response to TNF blocking agents in RA patients (15,(17)(18)(19)(20)(21)(22)(23). Most of the earlier studies evaluated small numbers of patients (17)(18)(19)(20)22) and/or joints (17,(19)(20)(21) and/or had short followup periods (17,18), which probably limited the ability to investigate the responsiveness and predictive value of US findings in RA patients treated with anti-TNF agents.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results were in accordance with those of previous longitudinal studies that have shown changes in CDUS or PDUS findings associated with clinical and laboratory response to TNF blocking agents in RA patients (15,(17)(18)(19)(20)(21)(22)(23). Most of the earlier studies evaluated small numbers of patients (17)(18)(19)(20)22) and/or joints (17,(19)(20)(21) and/or had short followup periods (17,18), which probably limited the ability to investigate the responsiveness and predictive value of US findings in RA patients treated with anti-TNF agents.…”
Section: Discussionsupporting
confidence: 93%
“…We chose a combination of grayscale and PD findings as imaging variables reflecting rheumatoid joint inflammation. In addition, as in the studies by Iagnocco et al (22,23), we included findings on periarticular inflammation in the PDUS assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations